The Acts of the Council of Chalcedon. 3 volumes. Translated with introduction and notes by Richard Price and MichaelGaddis - Wickham, L. R. (The journal of theological studies, 2008)
All the significant documents relative to the fourth ecumenical council appear here in English translation and annotation. Where discussion has advanced understanding since Schwartz the editors take due note, correct errors wisely, and introduce a number of important clarifications and suggestions of their own. I have sampled the translation; it is reliable. The annotation (excellent in scope), the introductions, the couple of appendices (‘The Documentary Collections’ and ‘Attendance and Ecumenicity’), a glossary, and important indexes will inform without overwhelming the historians to whom the work is by designation of the series intended.